Database encryption USING Transparent Data Encryption - Rahayu Noveandini Noveandini (JAKSTIK Journal, 2003)
ABSTRACTThe development of global data communications network providing challenges in data andinformation security. Sharing of methods are used to maintain the confidentiality of data,either from application or database level. There are three basic types of encryption, namelymanual, semi-transparent, and transparent. Transparent Data Encryption is one type ofencryption that has advantages in ease of the user because the user does not need to doencryption and decryption process management data directly because the database has to doit. This research will discuss the workings of Transparent Data Encryption, superiority, andits implementation in the encryption database. From this discussion of the benefits of EFTcan be known, such as performance degradation due to lack of data encryption and ease ofimplementation offered to the user.